Kajian Perencanaan Tebal Perkerasan Jalan Nasional Poros Bua – Rantepao - Ayukardona; Rais Rachman; Louise Elizabeth Radjawane (Paulus Civil Engineering Journal, 2021)
This research was conducted to redesign the flexible pavement thickness of the Bua – Rantepao road using the Road Pavement Design Manual method 2013 set by the Ministry of Public Works, Directorate General of Bina Marga in 2013. The acceleration of the improvement of Jalan Bua - Rantepao is carried out because there are many heavy vehicles that pass, causing the building to be more easily damaged and the presence of tourist objects that trigger the level of traffic congestion. The data collection was in the form of primary data on traffic conditions on Jalan Bua - Rantepao and ADT and secondary data in the form of CBR data. Based on the results of the research on pavement thickness planning using the Road Pavement Design Manual method 2013, the results obtained are design 3 pavement thicknesses with a surface layer of 40 mm thick AC-WC, 155 mm thick AC-BC, the top foundation layer using 150 mm thick CTB and the lower foundation layer using LPA class A with a thickness of 150 mm. If the CTB is difficult to implement or there are insufficient resources to do it, the solution is to use the 3A design, namely the AC-WC surface layer with a thickness of 40 mm, an AC-BC layer with a thickness of 60 mm and an AC-Base layer with a thickness of 80 mm. The thickness of the LPA class A sub-base layer is 300 mm thick. The effective method that can be used is the 2013 Bina Marga method, design 3A, 40 mm thick AC-WC surface layer, 60 mm thick AC-BC layer and 80 mm thick AC-Base. The thickness of the LPA class A sub-base layer is 300 mm thick.